2020
DOI: 10.21037/tau-20-1352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on the prognosis and recurrence of prostate cancer after radical prostatectomy: a meta-analysis

Abstract: Background: Obesity has been found to be closely related to the increased risk of fatal prostate cancer (PCa), however there remains no evidence that further clarifies the relationship between obesity and the postoperative recurrence and poor prognosis of PCa. In this study, a systematic review and meta-analysis were performed to systematically evaluate the effect of obesity on the prognosis and recurrence of PCa after radical prostatectomy (RP).Methods: A literature search of the PubMed, Web of Science, and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…They observed that smoking status modified the relationship between BMI and fatal PCa. Additionally, obesity may also be a risk factor for complications during surgery, and side effects from oncological treatment [50]. Furthermore, our study observed a lower risk of overall mortality among PCa cases with weight gain, which is in part supported by findings in the same study population who found that men with a weight loss had higher all-cause mortality [51].…”
Section: Discussionsupporting
confidence: 84%
“…They observed that smoking status modified the relationship between BMI and fatal PCa. Additionally, obesity may also be a risk factor for complications during surgery, and side effects from oncological treatment [50]. Furthermore, our study observed a lower risk of overall mortality among PCa cases with weight gain, which is in part supported by findings in the same study population who found that men with a weight loss had higher all-cause mortality [51].…”
Section: Discussionsupporting
confidence: 84%
“…Obesity affects more than 30% of the population in the U.S.A. ( Luo et al, 2020 ). The prevalence of overweight and obesity has increased ( Chooi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…We applied a 10 Mb clumping window with a rigorous r2 cutoff of 0.001 to remove SNPs in linkage disequilibrium and retained only those with the lowest P-value. Utilizing the PhenoScanner database, we screened and excluded SNPs associated with plausible confounders (tobacco smoking, alcohol consumption, and obesity (13)(14)(15)). Furthermore, we performed MR pleiotropy residual sum and outlier (MR-PRESSO) test before MR analysis to examine whether horizontal pleiotropy existed.…”
Section: Instrument Selectionmentioning
confidence: 99%